Henry Putney Beers papers - Beers, Henry Putney, 1907-
Correspondence, memoranda, writings, book reviews, reports, and other papers relating primarily to Beers's work as a bibliographer in American history. Also includes material pertaining to his career at the National Archives including his work with federal record surveys and an editorial project, Beers's life during the Great Depression, his naval service in World War II, and his doctoral advisor, St. George L. Sioussat.
Historian, bibliographer, and archivist with the National Archives. Died 1996.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Sioussat, St. George L. -- 1878-1960.; United States. -- National Archives and Records Service; United States. -- Navy -- Military life; United States. -- Works Progress Administration; Archival surveys; Depressions -- 1929 -- United States; Public records; World War, 1939-1945.; United States -- History -- Bibliography; United States -- Social life and customs -- 1918-1945.; Archivists; Bibliographers; Historians